Updated checklist of Balearic leaf beetles (Coleoptera: Chrysomelidae) - Petitpierre, Eduard; Sacarés, Antoni; Jurado-Rivera, José A. (Zootaxa, 2017)
The first updated checklist of Balearic leaf beetles (Chrysomelidae) since 1960 is presented here, evincing the presence of 118 species. This estimation is clearly lower than the 141 species reported in the only list available to date (Jolivet, 1953), and the dissimilarity is even more pronounced if we take into account that 22 new species have been added during this period. The possible explanations for these differences are discussed. The main island in the archipelago holds most of the species (Mallorca, 113 spp.), followed by Menorca (71 spp.), Eivissa (39 spp.) and Formentera (19 spp.). Thus, the Gymnesian islands (Mallorca and Menorca) are more species-rich than the Pityusic ones (Eivissa and Formentera). The number of species per island is significantly correlated with their respective areas not only for the Balearic but also for the much larger western Mediterranean islands of Corsica and Sardinia, and these abundances are not related with their nearness to the closest mainland. Among the different subfamilies and tribes, the Balearic flea-beetles (Alticinae) are clearly more prevalent whereas on the contrary, the Clytrini are less represented in comparison with the nearest mainland (Iberian Peninsula). The presented checklist includes four endemic species, Cryptocephalus majoricensis (Mallorca, Menorca and Formentera), C. tramuntanae (Mallorca), Cyrtonus majoricensis (Mallorca) and Timarcha balearica (Mallorca and Menorca). Furthermore, two adventitious species, Monoxia obesula and Epitrix hirtipennis of North American origin, have been reported for the first time in the Balearic Islands, in agreement with previous findings in other Mediterranean countries.